Enhanced Colorimetric Signal for Accurate Signal Detection in Paper-Based Biosensors - Dorin Harpaz; Evgeni Eltzov; Timothy S. E. Ng; Robert S. Marks; Alfred I. Y. Tok (Diagnostics, 2020)
Paper-based colorimetric biosensors combine the use of paper with colorimetric signal detection. However, they usually demonstrate lower sensitivities because a signal amplification procedure has not been used. Stopping the reaction of colorimetric signal generation is often used in lab-based assays in order to amplify and stabilize the colorimetric signal for detection. In this study, the generation of a stopped colorimetric signal was examined for accurate and enhanced signal detection in paper-based biosensors. The colorimetric reaction in biosensors is usually based on the interaction between the enzyme horseradish peroxidase (HRP) and a selected chromogenic substrate. The two most commonly used HRP substrates, 3,3’,5,5’-tetramethylbenzidine (TMB) and 2’-azinobis (3-ethylbenzothiazoline-6-sulfonic-acid) (ABTS), were compared in terms of their ability to generate a stopped colorimetric signal on membrane. The stopped colorimetric signal was visible for TMB but not for ABTS. Moreover, the generation of stopped colorimetric signal was dependent on the presence of polyvinylidene-difluoride (PVDF) membrane as the separation layer. With PVDF the colorimetric signal (color intensity) was higher (TMB: 126 ± 6 and ABTS: 121 ± 9) in comparison to without PVDF (TMB: 110 ± 2 and ABTS: 102 ± 4). The TMB stopped colorimetric signal demonstrated a more stable signal detection with lower standard deviation values. To conclude, a stopped colorimetric signal can be generated in paper-based biosensors for enhanced and accurate signal detection.